Conservation status of Apis mellifera ruttneri inferred from whole genome sequences - Pinto, M. Alice (2023)
Apis mellifera ruttneri is the native honey bee subspecies from the Maltese islands (Malta, Comino and Gozo). This African-lineage subspecies is adapted to the harsh environmental conditions and to the limited forage season of these islands. For many years, it was considered highly hybridized, due to the large and sustained importation of foreign subspecies, especially A. m. ligustica, perceived by many beekeepers as superior or for commercial reasons. Recent studies based on morphometry and mitochondrial DNA have suggested the occurrence of A. m. ruttneri, particularly in the main island. Conservation initiatives and a breeding program have been developed, but to date its conservation status is not fully known. As part of the MEDIBEES project, here, over 50 A. m. ruttneri georeferenced colonies collected from across Malta, as well as 50 several reference subspecies (A. m. ligustica, A. m. siciliana, A. m. iberiensis, A. m. sahariensis, and A. m. intermissa) were whole genome sequenced. The population structure and admixture were assessed from genome-wide single nucleotide polymorphisms using model and distance based-methods. The results show varying levels of admixture proportions of A. m. ruttneri with C-lineage honey bees across Malta but also a shared ancestry with the honey bees of north Africa, consistent with the putative natural colonization from Africa in ancient times.